Prevalence and associated factors of glaucoma in the Russian Ural Eye and Medical Study - Bikbov, Mukharram; Gilmanshin, Timur R.; Zainullin, Rinat M.; Kazakbaeva, Gyulli M.; Arslangareeva, Inga I.; Panda-Jonas, Songhomitra; Khikmatullin, Renat I.; Aminev, Said K.; Nuriev, Ildar F.; Zaynetdinov, Artur F.; Uzianbaeva, Yulia V.; Nikitin, Nikolay A.; et al. (Scientific reports, 2020)
To assess the prevalence and associated factors of glaucoma in a Russian population. The population-based Ural Eye and Medical Study included 5899 (mean age 59.0 ± 10.7 years; range 40-94 years). Glaucomatous optic neuropathy was diagnosed using International Society of Geographical and Epidemiological Ophthalmology (ISGEO) criteria. Among 5545 participants with assessable optic disc photographs, 246 individuals [4.4%; 95% confidence interval (CI) 3.9, 5.0] had glaucoma, with open-angle glaucoma (OAG) in 177 individuals (3.2%; 95% CI 2.7, 3.7) and angle-closure glaucoma (ACG) in 69 individuals (1.2; 95% CI 1.0, 1.5), with IOP > 21 mmHg in 79 (32.1%) patients, and with 80 (32.5%) patients on glaucoma therapy. Glaucoma prevalence increased from 3/485 (0.6%; 95% CI 0.0, 1.3) in the age group of 40-45 years to 33/165 (20.0%; 95% CI 13.8, 26.2) in the group aged 80 + years. Higher OAG prevalence correlated with older age [odds ratio (OR) 1.07; 95% CI 1.04, 1.09; P < 0.001], longer axial length (OR 1.36; 95% CI 1.17, 1.58; P < 0.001), higher intraocular pressure (IOP) (OR 1.18; 95% CI 1.13, 1.23; P < 0.001), higher stage of lens pseudoexfoliation (OR 1.26; 95% CI 1.08, 1.47; P = 0.004) and lower diastolic blood pressure (OR 0.98; 95% CI 0.96, 0.99; P = 0.035). Higher ACG prevalence correlated with older age (OR 1.07; 95% CI 1.03, 1.11; P < 0.001), narrower anterior chamber angle (OR 0.81; 95% CI 0.77, 0.86; P < 0.001), and higher IOP (OR 1.30; 95% CI 1.23, 1.38; P < 0.001). Glaucoma caused moderate to severe vision impairment (MSVI) in 9 (4.9%; 95% CI 1.8, 8.1) out of 184 individuals with MSVI (OAG, n = 7; ACG, n = 2), and blindness in one (9.1%) of 11 blind individuals. In this population from Russia, two thirds of glaucoma patients were not on therapy, and in two thirds of the glaucoma patients IOP was ≤ 21 mmHg. Otherwise, glaucoma prevalence, OAG-to-ACG ratio, and glaucoma associations did not differ markedly from Caucasian and East Asian populations.